MARKETING STRATEGY ANALYSIS IN AN EFFORT TO INCREASE THE NUMBER OF STUDENTS AT INSAN RABBANY BSD JUNIOR HIGH SCHOOL SOUTH TANGERANG CITY - Sulhan, Sulhan; Ahidin, Udin; Kasmad, Kasmad (Yayasan Education and Social Center, 2025)
This study aims to analyze the marketing strategy implemented by Insan Rabbany Junior High School, BSD, South Tangerang City, in an effort to increase the number of new students. The research method used is qualitative with data collection techniques of interviews, observation, and documentation. Data were analyzed using the 7P service marketing mix approach and SWOT analysis to identify strengths, weaknesses, opportunities, and threats and determine the appropriate strategy. The results show that the school implements an integrated Islamic curriculum-based marketing strategy with active promotion through social media, open houses, and the involvement of all school elements. Weaknesses are seen in limited parking facilities and a suboptimal school website. The SWOT analysis indicates a strategic position in the aggressive quadrant, so it is recommended to strengthen digital promotion, differentiate Islamic programs, involve alumni, and improve physical facilities. This research contributes to the development of marketing strategies in digital-based educational institutions.